Developing a Curriculum Alignment Model for Indonesia’s Merdeka Curriculum in Non-Formal Early Childhood Education - Elyana, Luluk; Munawar, Muniroh; Bhandari, Rahul (Journal of Nonformal Education, 2025)
Background:The development of a curriculum alignment management guide for Early Childhood Education (ECE) is essential to support curriculum adaptation in non-formal institutions such as Playgroups (KB) and Kindergartens (TK). In the context of curriculum changes, it is necessary to have a curriculum alignment model accompanied by effective management practices, ensuring that the adaptation process can be implemented systematically and effectively.Research Urgency:Curriculum changes at the ECE level require non-formal educational institutions, particularly KB and TK, to make curriculum adjustments. However, there is a lack of strategic and implementable management guides to support this process, especially for institutions that are unaccredited or minimally accredited. Thus, a valid and practical model guide is urgently needed.Research Objectives:This research aims to develop a curriculum alignment model for ECE equipped with a sound management guide, and to validate its feasibility for use by Heads of KB and TK in adapting the old curriculum to the new one.Research Method:The method employed is Research and Development (R&D) using the ADDIE model, which includes five stages: Analyze, Design, Development, Implementation, and Evaluation. Validation was conducted by two experts in the fields of language and curriculum management content to assess the strategic and implementative feasibility of the guide.Research Findings:The validation results showed a score of 4.4 for the language aspect and 4.0 for the management substance aspect, both categorized as very good. The trial implementation involving Heads of KB and TK in Tayu District, Pati Regency, resulted in an acceptance rate of 80.35%, which also falls into the very good category.Research Conclusion:The developed curriculum alignment model is feasible for use as a guide in aligning the PAUD curriculum. It provides strategic and implementative direction for carrying out curriculum adaptation within non-formal education institutions.Research Novelty/Contribution:This research introduces a new contribution in the form of a curriculum alignment management guide for ECE that is both strategic and implementable. It offers practical support for Heads of KB and TK, especially those with minimal or no accreditation, to manage curriculum changes in a more structured and effective manner.